2023
DOI: 10.1186/s13071-022-05647-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marker-free transgenic Chlamydomonas on the control of Aedes mosquito population and on plankton

Abstract: Background More than half of the world’s population suffers from epidemic diseases that are spread by mosquitoes. The primary strategy used to stop the spread of mosquito-borne diseases is vector control. Interference RNA (RNAi) is a powerful tool for controlling insect populations and may be less susceptible to insect resistance than other strategies. However, public concerns have been raised because of the transfer of antibiotic resistance marker genes to environmental microorganisms after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…on natural plankton was investigated in aquatic environments. As a result, it was reported that the reduction rates of plankton in the environment where transgenic algae were applied did not show a significant difference compared to the area where non-transgenic microalgae were applied ( Fei et al, 2023b ). Although transgenic microalgae have been shown to be highly effective in mosquito control, further studies are needed to investigate their toxic effects on the environment and non-target organisms.…”
Section: Resultsmentioning
confidence: 99%
“…on natural plankton was investigated in aquatic environments. As a result, it was reported that the reduction rates of plankton in the environment where transgenic algae were applied did not show a significant difference compared to the area where non-transgenic microalgae were applied ( Fei et al, 2023b ). Although transgenic microalgae have been shown to be highly effective in mosquito control, further studies are needed to investigate their toxic effects on the environment and non-target organisms.…”
Section: Resultsmentioning
confidence: 99%
“…The use of dsRNA for RNAi-mediated degradation of targeted mRNA has shown promise as a novel tool for RNA-based mosquito management strategies ( 16 , 28 ). However, there are still several challenges that needs to be addressed, such as the high cost of dsRNA production, inconsistent RNAi efficiency, and the nonsustainable delivery methods used to administer dsRNA to mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods have limited feasibility for large-scale field applications due to the high cost of dsRNA production and its rapid degradation in the environment. Recent studies have explored alternative approaches for delivering dsRNA to mosquitoes, such as using transgenic nonsymbiotic bacteria, yeast, or algae ( 14 16 ). However, these studies used microorganisms that cannot colonize the mosquito gut, resulting in transient gene knockdown and limited sustainable effects of RNAi technology.…”
Section: Introductionmentioning
confidence: 99%